Classifying Islamic Exegesis: How Muslim and Western Scholars Categorize Tafsir Traditions - Khodijah, Siti; Kholid, Abd. (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
The study of madha>hib al-tafsi>r is essential for understanding the historical development of Qur’anic exegesis as a scholarly discipline. The evolution of exegetical methodologies has been shaped by various historical, social, political, and epistemological factors, leading to the emergence of diverse interpretive approaches. This study examines the evolution and intellectual classification of madha>hib al-tafsi>r, focusing on the internal and external determinants that have influenced the methodological and thematic diversity of Qur’anic interpretation among Muslim and Western scholars. Employing a historical-critical approach combined with content analysis, this research investigates primary and secondary exegetical sources from both classical and contemporary Muslim and Orientalist scholars. The findings reveal that the evolution of madha>hib al-tafsi>r has been shaped by socio-political dynamics, theological discourse, evolving exegetical methodologies, and Islam’s intellectual engagement with other civilizations. The classification frameworks proposed by Muslim and Orientalist scholars reflect distinct epistemological paradigms in approaching the Qur’anic text, particularly concerning methodological principles, hermeneutical strategies, and ideological orientations. This study provides a more nuanced understanding of the historical trajectory of Qur’anic exegesis and its significance within contemporary Islamic scholarship. The findings underscore the importance of adopting a critical approach in assessing the development of tafsi>r and distinguishing the epistemological foundations of Muslim and Orientalist exegetical traditions.